Revisiting the tourism-led-growth hypothesis for Turkey using the bounds test and Johansen approach for cointegration - Katircioglu, Salih T. (Elsevier Sci Ltd, 2009)
This paper empirically revisits and investigates the tourism-led-growth (TLG) hypothesis in the case of Turkey by employing the bounds test and Johansen approach for cointegration using annual data from 1960-2006. Although Gunduz and Hatemi-J (2005; Is the tourism-led growth hypothesis valid for Turkey? Applied Economics Letters. 12, 499-504) support the TLG hypothesis for Turkey (suggesting unidirectional causation from tourism to economic growth) by making LIS(! of the leveraged bootstrap Causality tests, and Ongan and Demiroz (2005; The contribution of tourism to the long-run Turkish economic growth. Ekonomick casopis [Journal of Economics]. 53(9), 880-894.) suggest bidirectional causality between international tourism and economic growth in Turkey, this Study does not find any cointegration between international tourism and economic growth in Turkey. Therefore, unlike the findings of Gunduz and Hatemi-J (2005) and Ongan and Demiroz (2005), this study rejects the TLC hypothesis for the Turkish economy since no cointegration was found and error correction mechanisms Plus causality tests cannot be run for further steps in the long term. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Tourism-Led Growth; The Bounds Test; Cointegration; Turkey